2015
DOI: 10.1371/journal.pone.0143632
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte Scoring Enhances Embryo-Scoring in Predicting Pregnancy Chances with IVF Where It Counts Most

Abstract: ContextOur center’s quality improvement optimization process on many occasions anecdotally suggested that oocyte assessments might enhance embryo assessment in predicting pregnancy chances with in vitro fertilization (IVF).ObjectiveTo prospectively compare a morphologic oocyte grading system to standard day-3 morphologic embryo assessment.Design, Setting, PatientsWe prospectively investigated in a private academically-affiliated infertility center 94 consecutive IVF cycles based on 6 criteria for oocyte qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 28 publications
4
50
0
Order By: Relevance
“…Oocyte quality is an important factor that influences the developmental and implantation potential of derived embryos (Lazzaroni-Tealdi et al, 2015). In assisted reproduction, heterogeneity in oocyte quality is quite common.…”
Section: Introductionmentioning
confidence: 99%
“…Oocyte quality is an important factor that influences the developmental and implantation potential of derived embryos (Lazzaroni-Tealdi et al, 2015). In assisted reproduction, heterogeneity in oocyte quality is quite common.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that determining pregnancy potential at the oocyte level rather than the embryo level might provide an insight into the embryo selection for transfer. A previous Study suggested the oocyte scoring as a cheaper method than closed incubation systems with time-lapse photography [8]. Another research had focused on the embryo quality as the best for pregnancy chances, and had concentrated on improving embryo rather than oocyte assessment, which leads to increasing the cost as the closed automated incubation systems with time-lapse photography [9].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between oocyte quality, embryo development, and in-vitro fertilization (IVF) outcomes has been widely studied (Lazzaroni-Tealdi et al ., 2015). Some studies revealed that successful pregnancy outcome with IVF/intracytoplasmic sperm injection (ICSI) depended on several variables including oocyte and sperm quality (Savitha et al ., 2012; Braga et al ., 2013; Ebner et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Oocyte and embryo quality were assessed based on morphological features (Lazzaroni-Tealdi et al ., 2015; Braga et al ., 2013; ALPHA Scientists In Reproductive Medicine & ESHRE Special Interest Group Embryology, 2011). However, the correlation between these ''abnormal'' oocyte morphotypes, fertilization rates, and embryo development is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation